SOCIALIZATION OF MINISTRY OF FINANCE REGULATION No. 51 & 52 YEAR 2025 ABOUT GOLD TAX IN SURABAYA - Susanna Hartanto (PEDAMAS (PENGABDIAN KEPADA MASYARAKAT), 2026)
Minister of Finance Regulation Number 51 of 2025 regulates the collection of Article 22 Income Tax related to payments for the delivery of goods and activities in the import sector and other business activities. This regulation is an improvement on the previous provisions in Minister of Finance Regulation Number 81 of 2024. In addition to regulating the Article 22 Income Tax aspects of bullion business activities in the form of trading (bullion trading), by considering the principles of fairness and equality of treatment and providing administrative convenience, Minister of Finance Regulation 51 of 2025 also stipulates that purchases of gold bullion through imports or domestic purchases are subject to a uniform Article 22 Income Tax rate of 0.25%. Minister of Finance Regulation Number 52 of 2025 also reaffirms that the collection of Article 22 Income Tax is not carried out on the sale of gold bullion by gold jewelry and/or bullion entrepreneurs to certain parties. The parties exempted from the tax collection include: first, end consumers. Second, Taxpayers subject to final Income Tax. Third, Taxpayers who have a certificate of exemption from Article 22 Income Tax collection. Although there are legal regulations governing it, until now there are still many retail gold business actors in Surabaya who do not understand the tax on gold. This community service activity aims to provide material to retail gold business actors regarding the aspects of gold tax. The approach method used is  lecture and question and answer method. The target output of this community service activity is the implementation of legal counseling activities for retail gold business actors in Surabaya, and the results of this activity can be published through a community service journal.